1971
DOI: 10.1177/00220345710500013501
|View full text |Cite
|
Sign up to set email alerts
|

Identification of Actinomyces and Related Bacteria in Dental Calculus by the Fluorescent Antibody Technique

Abstract: Calculus specimens were examined by direct fluorescent antibody techniques and cultural procedures for the presence of gram-positive filamentous or diphtheroid bacteria. Actinomyces israelii, A viscosus, A naeslundii, Arachnia propionica, Rothia dentocariosa, Bacterionema matruchotii, and Corynebacterium acnes were observed in and cultured from the majority of specimens, with more than one species present in every specimen.Since fluorescent antibody (FA) techniques have been used to identify species of Actinom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
10
0

Year Published

1973
1973
2015
2015

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 40 publications
(10 citation statements)
references
References 9 publications
0
10
0
Order By: Relevance
“…Indeed, pleomorphic genera such as Aclinomyces almost certainly contribute to this category, just as they are likely contributors to the categories of straight rods and filaments. Although species of Actinomyces are frequently thought of as filamentous because of their appearance in culture, it is worthwhile to remember that in vivo they are most frequently rod-like or coccoid in shape (Snyder et al 1967, Slack et al 1971. In this connection it is interesting to note that a recent study of the cultivable subgingival flora of normal sulci has reported a predominance of either streptococci or Actinomyces in samples taken from seven individuals with clinical healthy gingivae (Slots 1977b).…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, pleomorphic genera such as Aclinomyces almost certainly contribute to this category, just as they are likely contributors to the categories of straight rods and filaments. Although species of Actinomyces are frequently thought of as filamentous because of their appearance in culture, it is worthwhile to remember that in vivo they are most frequently rod-like or coccoid in shape (Snyder et al 1967, Slack et al 1971. In this connection it is interesting to note that a recent study of the cultivable subgingival flora of normal sulci has reported a predominance of either streptococci or Actinomyces in samples taken from seven individuals with clinical healthy gingivae (Slots 1977b).…”
Section: Discussionmentioning
confidence: 99%
“…Histological evidence of the predoininanee oi Gram-positive filamentous microorganisms in calculus has been available for many years (Bibby 19.^.S,Yardeni 194cS,Hazen & Zander 19.59) but only recently have the species been identified (Slack et al 1971, Collins, Gerencser & Slaek 1973.…”
Section: Discussionmentioning
confidence: 99%
“…Older speeimens contained predominantly Actinomyces israelii and Actitwmyces naeslundii. However, with the exeeption of the Actinomycetaccae, isolated by cultural techniques and demonstrated microscopically by fluorescent antibody staining (Slack, Landfried & Gerencser 1971), most morphological types of microorganisms found in calculus have not been specifically identified.…”
Section: Sidawaymentioning
confidence: 99%
“…One technique for the rapid detection of specific micr-oor'ganisrns in clinical samples is immunofiuoreseence tnicroscopy (7), This tnethod has been previously ttsed to exatiiitie Actittotnyces sp, (8,25), Streptococcus mutans (5,9,10,11,13,16,18,26), and spirochetes (15) in dental plaque. Recently, this technique has been applied to the detection of putative periodontal pathogens and has been shown in comparative studies to exhibit a high level of sensitivity and specificity compared to bacterial culture (Table 1), (3,24,31), In addition, specific levels of B. gingivalis in subgingival dental plaque have been associated with periodontal disease and may be useful in distinguishing disease states fi-om carrier states (30),…”
Section: Introductionmentioning
confidence: 99%